Don't Shoot the Message: Regulating Disinformation Beyond Content - Clara Iglesias Keller (Direito Público, 2021)
This paper approaches regulatory strategies against disinformation with two main goals: (i) exploring the policies recently implemented in different legal contexts to provide insight into both the risks they pose to free speech and their potential to address the rationales that motivated them, and (ii) to do so by bridging policy debates and recent social and communications studies findings on disinformation. An interdisciplinary theoretical framework informs both the paper's scope (anchored on understandings of regulatory strategies and of disinformation) and the analysis of the legitimate motivations for states to establish statutory regulation that aims at disinformation. Departing from this analysis, I suggest an organisation of recently implemented and proposed policies into three groups based on their regulatory target: content, data, and structure. Combining the analysis of these three types of policies with the theoretical framework, I will argue that, in the realm of statutory regulation, state action is better off targeted at data or structure, as aiming at content represents disproportional risks to freedom of expression. Furthermore, content targeted regulation shows little potential to address the structural transformations on the public sphere of communications that, among other factors, influence current practices of production and spread of disinformation. – – Esse artigo aborda estratégias regulatórias contra a desinformaç\~ao com dois objetivos principais. O primeiro é explorar regulaç\~oes recentemente implementadas em diferentes contextos legais, com foco tanto nos riscos que representam para a liberdade de express\~ao, quanto no seu potencial para solucionar as quest\~oes que as motivaram. O segundo objetivo é fazer tal análise através de uma conex\~ao entre debates regulatórios e os recentes achados das ciências sociais e das ciências da comunicaç\~ao sobre desinformaç\~ao. Este marco teórico interdisciplinar informa tanto o escopo do artigo (ancorado em entendimentos de "estratégias regulatórias" e de "desinformaç\~ao") quanto a análise das motivaç\~oes legítimas para que os Estados estabeleçam regulaç\~ao estatutária que vise o combate à desinformaç\~ao. Partindo desta análise, eu sugiro uma organizaç\~ao de políticas recentemente implementadas e propostas em três grupos, de acordo com o alvo regulatório: conteúdo, dados e estrutura. Combinando a análise desses três tipos de políticas com o marco teórico, eu argumento que, no âmbito da regulamentaç\~ao estatutária, a aç\~ao estatal é melhor direcionada a dados ou estrutura, pois o objetivo de conteúdo n\~ao apenas representa riscos desproporcionais à liberdade de express\~ao, mas também mostra pouco potencial para abordar as transformaç\~oes estruturais nas comunicaç\~oes que marcam a esfera pública atual.
Keywords: 300; disinformation; regulation; regulatory strategies; fake news; digital platforms; desinformaç\~ao; regulaç\~ao; estratégias regulatórias; fake news; plataformas digitais